The Finances of the Hungarian Aristocracy in Boom and Recession: The Credit Transactions of the Prince Esterházy, Batthyány and Festetics Families at the Turn of the Eighteenth and Nineteenth Centuries - Kurucz, György (Historical Studies on Central Europe, 2021)
Based on primary sources, the present study is intended to reconstruct and analyze the process and levels of indebtedness of some of the outstanding Hungarian aristocratic families possessing large landed properties in the western region of Hungary, mainly in the Transdanubian counties. The author provides exact numerical data on the changes of the registered amounts of credit transactions, the stocks of assets and liabilities of the princely line of the Esterházy, Batthyány and the Keszthely branch of the Festetics families at the turn of the eighteenth and nineteenth centuries. He explores the various documents kept by the financial administrations of the families, including contemporary county mortgage records, which testify to an extremely lively lending and borrowing environment during the French Wars. The study concludes that devaluations and the financial crises of the Austrian Empire in the 1810s exerted an adverse effect on the finances of both the above families and contemporary ‘small investors’.